STRATEGIC FORESIGHT AS A TOOL FOR COUNTERING MODERN GLOBAL CHALLENGES TO ECONOMIC SECURITY AND INEQUALITY: EU EXPERIENCE FOR UKRAINE IN PROMOTING RESILIENCE AND SUSTAINABILITY - PANCHENKO, Volodymyr; REZNIKOVA, Nataliia; IVASHCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The aim of the article is to explore the potential of strategic foresight in countering contemporary global challenges to economic security and inequality, as well as to analyze the specifics of its use by EU institutions to promote sustainability and resilience. Foresight analysis is characterized as an opportunity to explore the potential consequences of trends that may have different combinations of impact on economic security. Foresight is defined as an integral analytical part of strategic forecasting, focused on forecasting and planning, which determines the opportunities and threats of long-term development, and also suggests strategies for solving problem situations. Strategic foresight differs from traditional planning in that it considers probable, possible, plausible, and preferred futures alike. In addition, while traditional planning tries to prevent failure, foresight encourages resilience, which is early detection and rapid recovery, making it adaptive for managing economic security. One of the most important results of the formation of the institutional infrastructure of foresight research in the EU can be considered the formation on the EU foresight network. The European Commission focuses its activities in the field of strategic foresight-forecasting of sustainable development in four interrelated areas: socio-economic, geopolitical, green and digital. The foresight analysis tools have been identified. The European strategy for economic security is analyzed and its priorities are highlighted. From the standpoint of sustainability and resilience, the problem of inequality both within the EU member states and within the association is emphasized, and the problem of digital inequality is highlighted. The socio-economic, geopolitical, environmental and digital dimensions of the economic security of the EU are characterized and the associated risks and threats are characterized. The foresight analysis of geopolitical risks is considered in the context of assessing the quality of policies. Attention is focused on the risks of cyber threats in the context of the digital transition as a megatrend that accompanies the formation of Industry 4.0, which will cause systemic changes that affect economic security. The problems that need to be solved by politicians both at the national and supranational levels in the implementation of green and digital transitions are noted. It is concluded that the development of economic, social, industrial, digital, environmental policies, by their nature, is based on taking into account development megatrends, but governments usually do not resort to proper scanning of unexpected, unprecedented events and effective response to them. In particular, policies that continue established or past trends and do not take new developments into account may be ineffective, inadequate or even counterproductive. Strategic foresight has become an important tool for shaping EU policy, developing sound forward-looking strategies and ensuring actions linked to long-term goals through the use of various technologies